Application of hedge algebras for controlling mechanisms of relative manipulation - Khoi, Phan Bui; Toan, Nguyen Van (Vietnam Journal of Science and Technology, 2017)
This paper presents a method for controlling mechanism of relative manipulation (MRM robot), that based on an algebraic approach to linguistic hedges in fuzzy logic. The proposed model of MRM robot is introduced as two component mechanisms, collaborating to realize technological manipulations. MRM robot has complex structure [1, [2]; therefore, robot system’s mathematical equations describing dynamical behaviors are complicated and voluminous [3,[4, 5]. Furthermore, the components affect MRM robot’s dynamics that are difficult to determine adequately and exactly. Applying the well-known methods (based on dynamical equations) such as PD/PID, computed torque algorithm...for robot control is difficult, especially with MRM robot. By dint of the human-like inference mechanism, designing controller thanks to fuzzy logic can overcome the mentioned drawbacks [6]. However, the linguistic variables in fuzzy logic are not represented by any physical values; and hence, the comparison between the linguistic variables is unable. Moreover, composition of fuzzy relations, defuzzification use approximation function which can trigger error in data process. Hedge Algebras(HA) gives favorable conditions to restrict fuzzy logic’s drawbacks because the linguistic labels in Hedge Algebras are represented by semantic values; and, composition of fuzzy relations and defuzzification are processed by simple interpolation and mapping functions. The obtained results from HA controller are compared to the obtained results from two methods which are presented in [6] (fuzzy controller and computed torque controller). Keywords: mechanism of relative manipulation (MRM robot), hedge algebras.